Application of Learning Media Live Worksheets in Writing Response Texts in Class VII.7 Students of SMP Negeri 15 Palembang - Houtman, Houtman; Salsabillah, Adella Rira; Lestari, Ayu; Lubis, Lili Fadila; Munawaroh, Nilam (STKIP PGRI Bandar Lampung, 2024)
This research aims to explore and test the effectiveness of the implementation of Live Worksheets as a technology-based learning tool in increasing student involvement and flexibility in delivering material in the SMP Negeri 15 Palembang environment. The research method used is qualitative. The subjects of this research were students in class VII.7 of SMP Negeri 15 Palembang with a total of 32 students. Data was collected through direct observation and tests. Data analysis is carried out by collecting data, reducing data, presenting data, and then drawing conclusions. The research results show the positive impact of implementing Live Worksheets learning media in learning to write response texts for class VII.7 students at SMP Negeri 15 Palembang. The implication of these findings for learning practice is that the use of digital learning media such as Live Worksheets can increase the effectiveness of writing learning in classroom VII.7 Public Middle School 15 Palembang. Keywords: learning media, LiveWorksheets, writing response-text